Lin28a is dormant, functional, and dispensable during mouse oocyte-to-embryo transition - Flemr, Matyas; Moravec, Martin; Libova, Veronika; Sedlacek, Radislav; Svoboda, Petr (Biology of reproduction, 2014)
The oocyte-to-embryo transition (OET) denotes transformation of a highly differentiated oocyte into totipotent blastomeres of the early mammalian embryo. OET depends exclusively on maternal RNAs and proteins accumulated during oocyte growth, which implies importance of post-transcriptional control of gene expression. OET includes replacement of abundant maternal microRNAs (miRNAs), enriched also in differentiated cells and exemplified by the Let-7 family, with embryonic miRNAs common in pluripotent stem cells (the miR-290 family in the mouse). Lin28a and its homolog Lin28b encode RNA-binding proteins, which interfere with Let-7 maturation and facilitate reprogramming of induced pluripotent stem cells. Both Lin28a and Lin28b transcripts are abundant in mouse oocytes. To test the role of maternal expression of Lin28a and Lin28b during oocyte-to-zygote reprogramming, we generated mice with oocyte-specific knockdown of both genes by using transgenic RNA interference. Lin28a and Lin28b are dispensable during oocyte growth because their knockdown has no effect on Let-7a levels in fully grown germinal vesicle (GV)-intact oocytes. Furthermore, transgenic females were fertile and produced healthy offspring, and their overall breeding performance was comparable to that of wild-type mice. At the same time, 2-cell embryos derived from transgenic females showed up-regulation of mature Let-7, suggesting that maternally provided LIN28A and LIN28B function during zygotic genome activation. Consistent with this conclusion is increased translation of Lin28a transcripts upon resumption of meiosis. Our data imply dual repression of Let-7 during OET in the mouse model, the selective suppression of Let-7 biogenesis by Lin28 homologs superimposed on previously reported global suppression of miRNA activity.
Keywords: blastomery; zygota; Zygote; DNA-Binding Proteins; RNA, Messenger, Stored; Let-7; voles; Cell Differentiation; rodents; RNA messenger skladovaná; těhotenství; RNA interference; transgenic/knockout model; Totipotent Stem Cells; mikro RNA; myši inbrední C57BL; RNA Interference; Embryo Culture Techniques; RNA-Binding Proteins; LIN28; oocyte; MicroRNAs; myši knockoutované; genome activation; zygote; Luciferases; RNAi; guinea pigs; luciferasy; Animals; Oocytes; ženské pohlaví; zvířata; oocyty; přenos embrya; mice; Pregnancy; proteiny vázající RNA; Mice, Knockout; DNA vazebné proteiny; rats; kultivace embrya; totipotentní kmenové buňky; buněčná diferenciace; Blastocyst; Blastomeres; Embryo Transfer; Female; Mice, Inbred C57BL; microRNA; early development; blastocysta